Tumor-infiltrating monocytic myeloid-derived suppressor cells mediate CCR5-dependent recruitment of regulatory T cells favoring tumor growth - Schlecker, Eva; Umansky, Viktor (The journal of immunology, 2012)
Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population of myeloid cells in cancer patients and tumor-bearing mice that potently inhibits T cell responses. During tumor progression, MDSCs accumulate in several organs, including the tumor tissue. So far, tumor-infiltrating MDSC subpopulations remain poorly explored. In this study, we performed global gene expression profiling of mouse tumor-infiltrating granulocytic and monocytic (MO-MDSC) subsets compared with MDSCs from peripheral blood. RMA-S lymphoma-infiltrating MO-MDSCs not only produced high levels of NO and arginase-1, but also greatly increased levels of chemokines comprising the CCR5 ligands CCL3, CCL4, and CCL5. MO-MDSCs isolated from B16 melanoma and from skin tumor-bearing ret transgenic mice also expressed high levels of CCL3, CCL4, and CCL5. Expression of CCR5 was preferentially detected on regulatory T cells (Tregs). Accordingly, tumor-infiltrating MO-MDSCs directly attracted high numbers of Tregs via CCR5 in vitro. Intratumoral injection of CCL4 or CCL5 increased tumor-infiltrating Tregs, and deficiency of CCR5 led to their profound decrease. Moreover, in CCR5-deficient mice, RMA-S and B16 tumor growth was delayed emphasizing the importance of CCR5 in the control of antitumor immune responses. Overall, our data demonstrate that chemokines secreted by tumor-infiltrating MO-MDSCs recruit high numbers of Tregs revealing a novel suppressive role of MDSCs with potential clinical implications for the development of cancer immunotherapies.